2019
DOI: 10.1039/c9qi00116f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of M-doped (M = Ag, Cu, In) Bi2Te3 nanoplates via a solvothermal method and cation exchange reaction

Abstract: Cation-doped Bi2Te3 nanoplates were prepared via a cation exchange reaction between a cation solution and a Bi2Te3 nanoplate colloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…As illustrated, the narrow-scan Bi4f spectrum of the neat BFO reveals two peaks located at 158.7 and 164.0 eV (Figure 4A), identified as Bi4f 7/2 and Bi4f 5/2, respectively. As reported in previous literature, this can be identified as Bi 3+ (Bai et al, 2019). The bonding energy of the element Bi4f was shifted to the lower angle with increasing the amount of doped Ca 2+ ions, because the introduction of Ca 2+ ions changes the chemical environment around the Bi 3+ ions.…”
Section: Resultssupporting
confidence: 66%
“…As illustrated, the narrow-scan Bi4f spectrum of the neat BFO reveals two peaks located at 158.7 and 164.0 eV (Figure 4A), identified as Bi4f 7/2 and Bi4f 5/2, respectively. As reported in previous literature, this can be identified as Bi 3+ (Bai et al, 2019). The bonding energy of the element Bi4f was shifted to the lower angle with increasing the amount of doped Ca 2+ ions, because the introduction of Ca 2+ ions changes the chemical environment around the Bi 3+ ions.…”
Section: Resultssupporting
confidence: 66%
“…31 The binding energy peaks of Bi 4f and Te 3d are positioned at 157.2, 162.5 eV and 575.8, 586.3 eV, which are in accordance with the classic research. 32 It was found that the valence states of Bi and Te in the BT-N are +3 and −2, which are the appropriate valences in Bi 2 Te 3 . It was concluded that the BT-N was successfully synthesized.…”
Section: Resultsmentioning
confidence: 98%
“…41 Its electronic and thermoelectric properties, along with its layered structure, can enable the construction of chip-scale thermoelectric coolers and generators. 10 Bi 2 Te 3 is also used for bulk thermoelectric devices, and processing procedures used to optimize performance include sintering nanoparticles to increase the grain boundary density 42 and introducing nanoscale scattering sites by adding dopants, [43][44][45] intercalants, 16,32,[46][47][48][49] heterointerfaces, 10 and nanoinclusions. 50 During the fabrication of devices, it is common to solder conductive contacts containing metals such as Al, Sn, and Cu onto Bi 2 Te 3 .…”
Section: Llmentioning
confidence: 99%